2020
DOI: 10.1016/j.jpeds.2019.09.077
|View full text |Cite
|
Sign up to set email alerts
|

Children with Congenital Heart Disease Are Active but Need to Keep Moving: A Cross-Sectional Study Using Wrist-Worn Physical Activity Trackers

Abstract: Objective To compare daily physical activity of children with congenital heart disease (CHD) with healthy peers measured using wearables bracelets in a large cohort. Additionally, subjectively estimated and objectively measured physical activity was compared. Study design From September 2017 to May 2019, 162 children (11.8 AE 3.2 years; 60 girls) with various CHD participated in a self-estimated and wearable-based physical activity assessment. Step-count and moderate-tovigorous physical activity were recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 38 publications
0
48
1
Order By: Relevance
“…Five (22,33,35,37,38,40) out of eight (25,27,30) studies with self-or parent-reported outcomes found significantly lower PA levels in children with CHD. In contrast, five of nine studies with accelerometer-assessed PA found no differences between cases and controls, (26,28,29,31,33) and three found lower PA levels only in subgroups of patients. (36,39,40) The only accelerometer study that described a general lower PA level in children with CHD had no control group but compared the data to normative data from healthy children and adolescents participating in the Amherst Health and Activity Study.…”
Section: Physical Activity and Sedentary Behaviour In Children With Chdmentioning
confidence: 71%
See 3 more Smart Citations
“…Five (22,33,35,37,38,40) out of eight (25,27,30) studies with self-or parent-reported outcomes found significantly lower PA levels in children with CHD. In contrast, five of nine studies with accelerometer-assessed PA found no differences between cases and controls, (26,28,29,31,33) and three found lower PA levels only in subgroups of patients. (36,39,40) The only accelerometer study that described a general lower PA level in children with CHD had no control group but compared the data to normative data from healthy children and adolescents participating in the Amherst Health and Activity Study.…”
Section: Physical Activity and Sedentary Behaviour In Children With Chdmentioning
confidence: 71%
“…All studies reported PA level, either expressed as time in PA, exercise frequency, score on a PA scale or expended energy. In addition, eight studies described the proportion of individuals meeting national or international PA recommendations, (24,26,28,29,31,34,36,37) while six studies also reported on the time spent sedentary. (26,29,31,33,34,37) In nine of the 18 (50%) studies, there were no statistically significant differences in PA level between children with CHD and age-matched healthy peers.…”
Section: Physical Activity and Sedentary Behaviour In Children With Chdmentioning
confidence: 99%
See 2 more Smart Citations
“…6 In addition, when present, these health problems can be mitigated by an active lifestyle. [1][2][3] Although the health benefits of physical activity are well recognized, evidence shows that some children with CHD do not practice enough physical activity to achieve the recommended levels, 7 and activity declines and sedentary behaviors increase with age in both genders. 5 Furthermore, levels of physical activity of children with CHD are lower than those in healthy children.…”
mentioning
confidence: 99%